Investigation of pharmacokinetics, tissue distribution and excretion of schisandrin B in rats by HPLC–MS/MS. (24th September 2017) - Wang, Zhuo; You, Linjun; Cheng, Yan; Hu, Kaiyong; Wang, Zhanbo; Cheng, Yanan; Yang, Jin; Yang, Yong; Wang, Guangji
Abstract: Schisandrin B has received much attention owing to its various biological activities. The present study was aimed at the formulation development of schisandrin B and investigation of the pharmacokinetic profiles, distribution and excretion of schisandrin B in Sprague–Dawley rats. In this study, micronized schisandrin B particles with particle size of 10–20 μm were chosen as the research object. Chromatographic separation was carried out on a BDS Hypersil C18 column (50 × 2.1 mm, i.d. 3.5 μm). Schisandrin B and deoxyschizandrin (internal standard) were detected without interference in the multiple reaction monitoring mode with positive electrospray ionization. The pharmacokinetic parameters were calculated by a noncompartmental method. The area under concentration–time curve and the maximum concentration showed a significant difference in gender. The calculated absolute oral bioavailability of schisandrin B was 55.0% for female rat and 19.3% for male rat. Schisandrin B exhibited linear pharmacokinetics properties within the range of the tested oral dose (10, 20 and 40 mg/kg). After oral administration of schisandrin B, it was extensively distributed in ovary and adipose tissue. The result also showed very low urinary, biliary and fecal excretion of schisandrin B implying that schisandrin B was excreted mainly in the forms of metabolites.